Case Law of the European Court of Human Rights on Freedom of Expression in the Online environment with Special Regard to Central Europe - Szinek, János (The ECHR at 70: The Central European Narrative, 2025)
The online space raises trending issues related to freedom of expression, such as fake news, radical and extremist content, hate speech, and even excessive limitations imposed by the platforms. This new digital environment poses several unique challenges for the European Court of Human Rights: it is exceedingly complicated to consider all the specific features of the digital realm alongside the basic principles outlined in the Article 10 of the European Convention on Human Rights. Since the European Court of Human Rights serves as the most important interpreter of human rights standards in Europe, it plays a vital role in interpreting the right to freedom of expression in the digital environment. The case law of the European Court of Human Rights also affects its territorial jurisdiction, making the court an influential norm entrepreneur. This paper aims to analyse three crucial cases of the European Court of Human Rights concerning liability for comments and hyperlinking in the online space. Keywords: online platforms, freedom of expression, liability for comments, liability for hyperlinking, European Court of Human Rights